Progress of prevention and nursing of mechanical phlebitis associated with peripherally inserted central venous catheter placement (PICC置管所致机械性静脉炎的防治及护理进展) - JIAO Lijuan (焦丽娟) (中西医结合护理)
The peripherally inserted central venous catheter (PICC) has advantages of minimal invasion, long indwelling time and high safety, and has been widely use in clinical practice. The mechanical phlebitis development is influenced by PICC placement method, operation environment for catheter placement and technique for the operation, affecting the patient's treatment. This paper reviewed the studies about prevention and nursing of mechanical phlebitis associated with PICC placement, and provided reference for clinical practice. (经外周静脉穿刺中心静脉置管(PICC)具有创伤小、留置时间长、安全性高等优势, 临床应用广泛。PICC置管受操作方法、操作环境以及操作人员的水平和技术等因素影响, 可能会发生机械性静脉炎, 进而影响患者的治疗过程。本文就PICC置管所致机械性静脉炎的防治问题进行综述, 以期为临床干预提供参考。)